ANALISIS PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, KEPERCAYAAN, DAN NILAI NASABAH TERHADAP CUSTOMER RETENTION DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING PADA PT BANK BRISYARIAH KANTOR CABANG PEMBANTU UNGARAN - Fatmawati, Ratih; handayani, jati (Jurnal Sains Ekonomi dan Perbankan Syariah, 2015)
AbstractTheÂ researchâsÂ aimÂ toÂ analyzeÂ theÂ influenceÂ significantÂ variableÂ ofÂ serviceÂ quality,Â serviceÂ product,Â trust,Â andÂ customerÂ valueÂ towardÂ customerÂ retentionÂ withÂ customerÂ satisfactionÂ asÂ interveningÂ inÂ theÂ PTÂ BankÂ BRIShariaÂ UngaranÂ BranchÂ Office.TheÂ populationÂ inÂ thisÂ researchÂ wereÂ allÂ ofÂ savingÂ customersÂ inÂ theÂ PTÂ BankÂ BRIShariaÂ UngaranÂ BranchÂ Office.Â TheÂ samplingÂ techniqueÂ wereÂ usedÂ judgmentalÂ samplingÂ method.Â TheÂ samplesÂ inÂ thisÂ researchÂ wereÂ 145Â savingÂ customersÂ PTÂ BankÂ BRIShariaÂ UngaranÂ BranchÂ Office.Â ModelÂ ofÂ analysisÂ inÂ thisÂ researchÂ usingÂ StructuralÂ EquationÂ ModelÂ (SEM).Â WhileÂ theÂ analysisÂ techniquesÂ inÂ thisÂ studyÂ usingÂ tÂ testÂ withÂ computerÂ programÂ AMOSÂ 22.0.TheÂ resultÂ inÂ thisÂ researchÂ showedÂ thatÂ serviceÂ qualityÂ influencesÂ positiveÂ andÂ significantÂ towardÂ customerÂ satisfaction,Â productÂ qualityÂ influencesÂ positiveÂ andÂ significantÂ towardÂ customerÂ satisfaction,Â trustÂ influencesÂ positiveÂ andÂ significantÂ towardÂ customerÂ satisfaction,Â customerÂ valueÂ influencesÂ negativeÂ andÂ notÂ significantÂ Â towardÂ customerÂ satisfaction,Â andÂ customerÂ satisfactionÂ influencesÂ positiveÂ andÂ significantÂ towardÂ customerÂ retention.Keywords:ServiceÂ Quality,Â ProductÂ Quality,Â Trust,Â CustomerÂ Value,Â CustomerÂ Satisfaction,Â andÂ CustomerÂ Retention.